2018
DOI: 10.4172/2574-0407.1000141
|View full text |Cite
|
Sign up to set email alerts
|

Magnitude and Impact of Occupational Related Needle Stick and Sharp Injuries and Associated Factors among Health Care Workers in Dire Dawa, Eastern Ethiopia

Abstract: Background: In African countries including Ethiopia occupational exposure of needle stick and sharp injuries is higher than elsewhere and it is still a major public health problem. It accounts for 86% of all occupationally related infection transmissions; expose Health Professionals to more than 20 blood borne pathogens. In Dire Dawa, Ethiopia, the magnitude of needle stick and sharp injuries and its health impacts remain unknown. In addition, available statistics underestimate the severity of the problem beca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
19
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 15 publications
5
19
1
Order By: Relevance
“…The earliest study was conducted during 2009 [55], and the latest two articles were published in 2019 [58, 59]. Overall information regarding the prevalence of NSIs was obtained from five regions and two self-administrative cities including Amhara [41, 44, 47, 49, 51, 53, 5759]; Oromia [42, 48, 56]; Southern Nations, Nationalities, and People (SNNP) [37, 46, 50]; Somali [38]; and Harari [43]; two studies were conducted on both Somali and Dre Dawa (SAC) [52, 55], and four articles were obtained from two self-administrative cities Addis Ababa and Dire Dawa [39, 40, 45, 54]. The sample size across the studies was ranged from 162 [37] to 760 [46].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The earliest study was conducted during 2009 [55], and the latest two articles were published in 2019 [58, 59]. Overall information regarding the prevalence of NSIs was obtained from five regions and two self-administrative cities including Amhara [41, 44, 47, 49, 51, 53, 5759]; Oromia [42, 48, 56]; Southern Nations, Nationalities, and People (SNNP) [37, 46, 50]; Somali [38]; and Harari [43]; two studies were conducted on both Somali and Dre Dawa (SAC) [52, 55], and four articles were obtained from two self-administrative cities Addis Ababa and Dire Dawa [39, 40, 45, 54]. The sample size across the studies was ranged from 162 [37] to 760 [46].…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, seven studies exclusively reported the lifetime prevalence of the NSI [37, 39, 40, 47, 54, 57, 58]. The remaining five articles have reported both the 12-month and lifetime needlestick injury prevalence [43, 45, 46, 48, 49, 59]. The quality of each of the included studies was evaluated using a nine-item risk of bias assessment tool [36].…”
Section: Resultsmentioning
confidence: 99%
“…This finding is consistent with studies conducted in Ethiopia, Egypt, Tanzania and Tehran. [24][25][26][27][28] The possible reason might be less experienced workers are in a stressful situation in the workplace, they are less likely to get training, they did not know how to process and handle used sharp instruments, and even they might not be much concerned about the consequence of injury compared to experienced workers.…”
Section: Discussionmentioning
confidence: 99%
“…All the included studies were cross-sectional studies and the sample size ranged from 232 [ 26 ] to 1125 [ 27 ]. Regarding the regional distribution of the included studies, 4 were conducted in the Oromia region [ 26 , 28 – 30 ], 3 in the Amhara region [ 22 , 27 , 31 ], 5 in Addis Ababa [ 33 – 37 ], 2 in the Southern Nations, Nationalities and Peoples Region (SNNPR) [ 38 , 39 ], and 1 study in Diredawa [ 40 ]. Among the included studies, the prevalence of full-dose hepatitis B vaccination coverage among health care workers ranged from 1.3 [ 26 ] to 62.7 [ 38 ] ( Table 1 )…”
Section: Methodsmentioning
confidence: 99%